2022
DOI: 10.1016/j.jss.2021.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Injury Under COVID-19 Stay-at-Home Advisory: Experience of a New England Trauma Center

Abstract: BACKGROUND With the onset of the COVID-19 pandemic and subsequent widespread stay-at-home advisories throughout early 2020, hospitals have noticed a decrease in illnesses unrelated to COVID-19. However, the impact on traumatic injury is relatively unknown. This study aims to characterize patterns of trauma during the COVID-19 pandemic at a Level I Trauma Center. MATERIALS & METHODS A retrospective review was performed of adult trauma patients from March through June, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 10 publications
5
13
0
Order By: Relevance
“…Multiple studies examining trauma during COVID‐19 have reported a drop in the number of minor injuries and a reduction in MVAs. 40 , 41 , 42 , 43 , 44 , 45 Despite this, studies focusing on patients with more severe injuries have reported that severe injury mechanisms in the COVID‐19 era remain similar to pre‐COVID‐19 era; our study includes only mortality patients, a population who naturally had sustained more severe injuries and its findings are consistent with previously published studies focusing on severe trauma. 15 , 46 , 47 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Multiple studies examining trauma during COVID‐19 have reported a drop in the number of minor injuries and a reduction in MVAs. 40 , 41 , 42 , 43 , 44 , 45 Despite this, studies focusing on patients with more severe injuries have reported that severe injury mechanisms in the COVID‐19 era remain similar to pre‐COVID‐19 era; our study includes only mortality patients, a population who naturally had sustained more severe injuries and its findings are consistent with previously published studies focusing on severe trauma. 15 , 46 , 47 …”
Section: Discussionsupporting
confidence: 89%
“…39 Multiple studies examining trauma during COVID-19 have reported a drop in the number of minor injuries and a reduction in MVAs. [40][41][42][43][44][45] Despite this, studies focusing on patients with more severe injuries have reported that severe injury mechanisms in the COVID-19 era remain similar to pre-COVID-19 era; our study includes only mortality patients, a population who naturally had sustained more severe injuries and its findings are consistent with previously published studies focusing on severe trauma. 15,46,47 The arrival mode of patients to our center showed significant changes in the pandemic period, with a higher number being transported by EMS/HEMS and transferred from other facilities, and a lower number period.…”
Section: Matched Period Subgroup Analysissupporting
confidence: 87%
“…Studies indicated a general increase in injuries caused by assault and self-harm, with similar results regarding other injury mechanisms such as sports-related injuries ( 23-26 ) and other less common mechanisms. However, a statistically significant increase in cases of firearm-related injuries and intentional or accidental stabbings was observed [for instance, a significant increase in gun-related injuries was observed, 6 vs. 9%, in a study by Mokhtari et al ( 27 )]; most of the findings in the present study came from studies conducted in the USA, where firearm legislation is more relaxed ( 23-43 ).…”
Section: Psychological Impact Of the Pandemic On Traumamentioning
confidence: 54%
“…The current literature on trauma volume and distribution during the pandemic varies by site with some sites having similar overall volume, 39 some with stable volume and increased penetrating percentage, 15 , 16 and others having overall decreased volume but increased rates of penetrating injury. 11 , 14 This study's results fit into the second group, and despite relative increased penetrating volume by 32%, and 25% increase in requiring initial operative intervention, mortality remained stable at 3.7%.…”
Section: Discussionmentioning
confidence: 99%